1984
DOI: 10.1300/j082v10n01_07
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Sexual Beliefs, Attitudes, Experience, and Homophobia

Abstract: Male and female subjects were given a series of questionnaires to assess their attitudes, behaviors, and experiences in relation to homosexuality. The findings indicated the presence of two systems, one dealing with affective orientation and the other with general beliefs (learned problem or physiological problem) about the origins of homosexuality. It was found that the greatest dislike toward homosexuals existed in those subjects who responded with negative affect and believed that homosexuality was a learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 0 publications
8
62
0
1
Order By: Relevance
“…Other studies used forced choice items between biological determinism, or non-controllability on the one hand and free choice, or changeability, on the other (e.g., Herek & Capitiano, 1995;Schmalz, 1993). Aguero et al (1984) presented three belief items about genetic determinism, homosexuals being able to ''help being the way they are,'' and the possibility of therapy changing homosexual preference. All three items subsequently loaded on a single factor.…”
Section: Sexual Orientation Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies used forced choice items between biological determinism, or non-controllability on the one hand and free choice, or changeability, on the other (e.g., Herek & Capitiano, 1995;Schmalz, 1993). Aguero et al (1984) presented three belief items about genetic determinism, homosexuals being able to ''help being the way they are,'' and the possibility of therapy changing homosexual preference. All three items subsequently loaded on a single factor.…”
Section: Sexual Orientation Beliefsmentioning
confidence: 99%
“…More direct support for this argument can be found in the empirical literature on antigay attitudes itself. Aguero, Bloch, and Byrne (1984) found that students who held genetic determinist beliefs were more tolerant than students who believed that sexual orientation was freely chosen. In a national sample of Black Americans, Herek and Capitiano (1995) found that respondents who believed homosexuality to be biological rather than chosen were also more tolerant.…”
mentioning
confidence: 98%
“…Desde los años setenta se han desarrollado diversas escalas para medir la homofobia manifiesta o tradicional como son las siguientes: Smith Homophobia Scale (Smith, 1971), Index of Homophobia (Hudson y Ricketts, 1980), Heterosexual Attitudes toward Homosexuality Scale (Larsen, Reed y Hoffman, 1980), Homophobia Scale (Hasen, 1982), Homophobia Scale (Aguero, Bloch y Byrne, 1984) y Homophobia Scale (Wright, Adams y Bernat, 1994). Sin embargo, la tendencia de los últimos años es que las escalas que miden la homofobia sean capaces de captar tanto las actitudes homófobas explícitas (tradicionales) como las actitudes homófobas sutiles o modernas como lo hacen las anales de psicología, 2013, vol.…”
Section: Introductionunclassified
“…Second, college-level curricula typically draw on textbooks that present evidence that sexual orientation is under biological control (Barker, 2007). Third, many surveys have found that heterosexual people who score lower on measures of sexual prejudice consider sexual orientation to be biologically determined or fixed, rather than learned or freely chosen (Aguero, Block, & Byrne, 1984;Eldridge, Mack, & Swank, 2006;Ernulf, Innala, & Whitam, 1989;Haslam & Levy, 2006;Haslam Rotschild, & Ernst, 2002;Hegarty, 2002;Hegarty & Pratto, 2001;Herek & Capitanio, 1995;Horvath & Ryan, 2003;Jayaratne, Ybarra, Sheldon, Brown, Feldbaum, Pfeffer, & Petty, 2006;Malcomnson, Christopher, Franzen, & Keyes, 2006;Sakalli, 2002;Whitley, 1990).…”
mentioning
confidence: 99%